2011
DOI: 10.3109/17435390.2011.562325
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of gold nanoglycodendrimers with algal cells (Chlamydomonas reinhardtii) and their effect on physiological processes

Abstract: With the rise of nanotechnologies, the risk of contamination of aquatic ecosystems with nanoparticles is increasing. Glycodendrimer-coated gold nanoparticles have been developed for biomedical applications; however, their effect on microalgae has never been studied. In this report, their interactions with algae were investigated using two strains of Chlamydomonas reinhardtii, a wild type having cell wall and a cell wall-deficient mutant. Cultures were exposed 48 h to 6 and 12 ng ml⁻¹ of gold nanoparticles coat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(42 citation statements)
references
References 45 publications
2
36
0
4
Order By: Relevance
“…CuO NPs can also located inside cells of C. reinhardtii (Perreault et al, 2012a) and polymer coated showed more distribution inside cell and more toxicity than bare CuO NPs. Some researches showed that gold (Au) NPs penetrated in the plasmic membrane of C. reinhardtii (Perreault et al, 2012b) and Scenedesmus subcapitata (Renault et al, 2008). Our results is the first report about finding TiO 2 NPs penetrate into cytoplasm which may be essential to asset risk of TiO 2 trnasfer through the trophic chain.…”
Section: Discussionmentioning
confidence: 55%
“…CuO NPs can also located inside cells of C. reinhardtii (Perreault et al, 2012a) and polymer coated showed more distribution inside cell and more toxicity than bare CuO NPs. Some researches showed that gold (Au) NPs penetrated in the plasmic membrane of C. reinhardtii (Perreault et al, 2012b) and Scenedesmus subcapitata (Renault et al, 2008). Our results is the first report about finding TiO 2 NPs penetrate into cytoplasm which may be essential to asset risk of TiO 2 trnasfer through the trophic chain.…”
Section: Discussionmentioning
confidence: 55%
“…C. reinhardtii growth was not inhibited by 50% at 10.11 mg L À1 , which was the highest exposure concentration tested in this study. The toxicity of AuNPs in C. reinhardtii was reported by Perreault et al (2011Perreault et al ( , 2012. The 24-h EC 10 and EC 50 values of AuNPs (2 nm) were 16 ± 17 and 83 ± 26 mg L À1 (Perreault et al, 2012).…”
Section: Characterization Of Aunpsmentioning
confidence: 93%
“…Direct NPs effects may be also associated with the induction of oxidative stress (von Moos and Slaveykova, 2014), membrane deterioration (Wang et al, 2011a(Wang et al, , 2011b and decreased cellular exchanges with the media due to particles binding on cell membrane (Lin et al, 2009, Perreault et al, 2012a. For instance, Cu NPs can cause oxidative stress and production of ROS (Kim et al, 2012;Perreault et al, 2014).…”
Section: Figmentioning
confidence: 99%